2021
DOI: 10.1021/acsomega.1c03705
|View full text |Cite
|
Sign up to set email alerts
|

ZnFe2O4@WO3–X/Polypyrrole: An Efficient Ternary Photocatalytic System for Energy and Environmental Application

Abstract: Environmental protection and the necessity of green energy have become fundamental concerns for humankind. However, rapid recombination of photoexcitons in semiconductors often gets in the path of photocatalytic reactions and annoyingly suppresses the photocatalytic activity. In this study, a polypyrrole (PPY)-supported step-scheme (S-scheme) ZnFe2O4@WO3–X (PZFW15) ternary composite was fabricated by a multistep process: hydrothermal and calcination processes, followed by polymerization. During the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…As a result, the appropriate electrons with reduction potential are retained at the conduction position of the RP, and similarly, the holes with high oxidation abilities are engaged at the valence position of the OP respectively, leading to an effective and improved electron−hole separation. 22,23,43,52 The S-scheme heterojunction is found to be an important replacement to the restriction imposed by prior photoactive mechanisms on the basis of utilizing two or more semiconductors joined together by different techniques. Moreover, the photoproduced electron from semiconductor 1 (SC1) or OP with lower conductionband (CB) potential will interact with photoproduced holes from semiconductor 2 (SC2) or RP with higher valence-band (VB) and will be dissipated at the interface.…”
Section: Development Of Heterojunction- Z-scheme- and S-scheme-based ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the appropriate electrons with reduction potential are retained at the conduction position of the RP, and similarly, the holes with high oxidation abilities are engaged at the valence position of the OP respectively, leading to an effective and improved electron−hole separation. 22,23,43,52 The S-scheme heterojunction is found to be an important replacement to the restriction imposed by prior photoactive mechanisms on the basis of utilizing two or more semiconductors joined together by different techniques. Moreover, the photoproduced electron from semiconductor 1 (SC1) or OP with lower conductionband (CB) potential will interact with photoproduced holes from semiconductor 2 (SC2) or RP with higher valence-band (VB) and will be dissipated at the interface.…”
Section: Development Of Heterojunction- Z-scheme- and S-scheme-based ...mentioning
confidence: 99%
“…Further, the combined PS (reduction unit and oxidation unit) has a staggered band arrangement with the Fermi state and the CB position of the reduction PS at a higher value compared to oxidation PS . The authors’ group also reported an S-scheme oriented photocatalyst for energy generation and environmental remediation. , Recently, H 2 O 2 has been a rising star in the clean energy field as it acts as both reductant and oxidant in one-compartment fuel cell with a theoretical potential output of 1.09 V, which is nearly that of the H 2 cell potential, i.e., 1.23 V. Moreover, its high water solubility and facile transportable nature along with nontoxic combustion side products make peroxide an absolute and potent energy carrier standby for the H 2 fuel economy . Interestingly, photocatalytic H 2 O 2 generation through oxygen reduction reaction is considered an environmentally benign and emerging approach that can effectively substitute the multistep, energy intensive, and toxic byproducts-generating anthraquinone method that accounts for about 95% of total industrial production .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research have been focused on the introduction of conducting polymers containing π-conjugated frameworks such as polyaniline (PANI), polyindole (PIn), polythiophene (PTs), and polypyrrole (PPy) for environmental remediation, which exhibit the advantages of both stopping the agglomeration of nanosheets and increasing the optical properties of the material . Among these four, polypyrrole is a potential candidate in photocatalysis and electrocatalysis owing to its excellent biocompatibility, good electrical conductivity, and ability to absorb visible light. , Moreover, in a PPy supported heterostructure photocatalyst, PPy can act as electron and hole acceptors, further improving the charge-carrier transportation and separation in the photocatalyst …”
Section: Introductionmentioning
confidence: 99%
“…35,36 Moreover, in a PPy supported heterostructure photocatalyst, PPy can act as electron and hole acceptors, further improving the chargecarrier transportation and separation in the photocatalyst. 37 The band gap engineering is of significance to generate an effective photocatalytic system with desired band structure in heterostructure nanocomposites. Based on the various advantages discussed above, herein an eco-friendly and robust photocatalyst consisting of conducting polymer polypyrrole, γ-FeOOH nanosheets, and CD semiconductor heterostructures has been developed via a simple in situ synthesis at room temperature (20 °C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…22−24 However, due to the rapid recombination of photo generated excitons in the spinel crystal structure, the photocatalytic potential of ZnFe 2 O 4 did not meet the expected target. Therefore, previous extensive efforts have been made in modifying ZnFe 2 O 4 , such as designed ZnFe 2 O 4 /g-C 3 N 4 n−n heterojunction, 25,26 ZnFe 2 O 4 @WO 3 S-scheme type heterojunction, 27,28 and so on. However, to the best of our knowledge, there is currently little research on the photocatalytic mechanism of ZnFe 2 O 4 under external magnetic fields.…”
Section: Introductionmentioning
confidence: 99%